Non-enzymatic glycosylation of a type 1 collagen matrix: effects on osteoblastic development and oxidative stress - McCarthy, Antonio Desmond (2001)
Background : The tissue accumulation of protein-bound advanced glycation endproducts (AGE) may be involved in the etiology of diabetic chronic complications, including osteopenia. The aim of this study was to investigate the effect of an AGE-modified type I collagen substratum on the adhesion, spreading, proliferation and differentiation of rat osteosarcoma UMR106 and mouse nontransformed MC3T3E1 osteoblastic cells. We also studied the role of reactive oxygen species (ROS) and nitric oxide synthase (NOS) expression on these AGE-collagen mediated effects. Results: AGE-collagen decreased the adhesion of UMR106 cells, but had no effect on the attachment of MC3T3E1 cells. In the UMR106 cell line, AGE-collagen also inhibited cellular proliferation, spreading and alkaline phosphatase (ALP) activity. In preosteoblastic MC3T3E1 cells (24-hour culture), proliferation and spreading were significantly increased by AGE-collagen. After one week of culture (differentiated MC3T3E1 osteoblasts) AGE-collagen inhibited ALP activity, but had no effect on cell number. In mineralizing MC3T3E1 cells (3-week culture) AGE-collagen induced a decrease in the number of surviving cells and of extracellular nodules of mineralization, without modifying their ALP activity. Intracellular ROS production, measured after a 48-hour culture, was decreased by AGE-collagen in MC3T3E1 cells, but was increased by AGE-collagen in UMR106 cells. After a 24-hour culture, AGE-collagen increased the expression of endothelial and inducible NOS, in both osteoblastic cell lines. Conclusions: These results suggest that the accumulation of AGE on bone extracellular matrix could regulate the proliferation and differentiation of osteoblastic cells. These effects appear to depend on the stage of osteoblastic development, and possibly involve the modulation of NOS expression and intracellular ROS pathways.